Kajian Strategi Promosi Digital Area Peternakan Kawasan Glugur Rimbun Kecamatan Kutalimbaru - Lubis, Hidayati Purnama; Riska Franita; Purwo Siswoyo; Putri Suci Rahayu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The purpose of this study was to determine the public's interest in visiting the Livestock Area of the Glugur Rimbun Area, Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, through the independent variables of promotion and attractiveness. This Animal Husbandry Area is one of several areas in the Al Amin Science and Industrial Park (Living Lab) Glugur Rimbun Area with a special land area for the Animal Husbandry Area of about two ha from the total area of about 24 (twenty four) ha. The research approach uses quantitative methods involving 100 respondents and data collection using questionnaires. The data obtained was analyzed using multiple regression analysis using SPSS. The results showed that the independent variable promotion showed a t-count value of -0.945 < t-table 1.984 with a significant value of 0.000 < 0.05, which means that digital-based promotion has a positive and significant effect partially on visiting interest. The test results for the attraction variable show a tcount value of 12.315> t-table 1.984 with a significant value of 0.000 <0.05, which means that attraction has a positive and significant effect partially on visiting interest. The F-count value of 75.864> F-table of 3.09 and a significant 0.000 <0.05, then digital-based promotion and attractiveness have a positive and significant effect simultaneously on tourist interest in visiting.